2017
DOI: 10.1097/rct.0000000000000557
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Patient Diameter on the Dual-Energy Ratio of Selected Contrast-Producing Elements

Abstract: Objectives To assess whether the low- to high-kVp CT number ratio at dual-energy CT (DECT) is affected by changes in patient diameter. Methods Seven contrast-producing elements were housed sequentially within an abdomen phantom. Fat rings enlarged the phantom diameter from 26 to 45 cm. The phantom was scanned using single-energy CT (SECT) at tube potentials of 80 and 140 kVp, and rapid-kVp-switching DECT. Results CT numbers decreased proportionally (~20% CT number reduction for smallest to largest phantom … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…This tungsten compound is not viable for development due to toxicity, but is inexpensive, water soluble, and has the same X-ray attenuation characteristics as potentially viable tungsten-based agents. The contrast materials were formulated in distilled water to concentrations of 10 mg/mL of the active element (20, 26, 27) which provided a contrast enhancement of ~280 HU for both elements at 120 kVp. Although higher contrast enhancement in the coronary arteries can be achieved clinically (28), we chose a relatively low concentration of 10 mg/mL for two reasons.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…This tungsten compound is not viable for development due to toxicity, but is inexpensive, water soluble, and has the same X-ray attenuation characteristics as potentially viable tungsten-based agents. The contrast materials were formulated in distilled water to concentrations of 10 mg/mL of the active element (20, 26, 27) which provided a contrast enhancement of ~280 HU for both elements at 120 kVp. Although higher contrast enhancement in the coronary arteries can be achieved clinically (28), we chose a relatively low concentration of 10 mg/mL for two reasons.…”
Section: Methodsmentioning
confidence: 99%
“…In our study the ratio ranges were defined as 0.5 – 1.2, for tungsten, 1.4 – 1.6 for calcium, and 1.8 – ∞ for iodine. These ratio ranges were approximated from different literature sources (25, 33, 34) and validated empirically for the phantom set-up used. For the three image datasets, 60 keV, 80 keV and 67 keV were used for the E1, E2 and E3 inputs respectively.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Generally, imaging patients especially those with larger body sizes requires high voltages (100–140 KeV). It has been reported that Ta (K‐edge 67 KeV) has enhanced CT contrast at ≈100 KeV and Au (K‐edge 81 Kev) shows high contrast at around 120 KeV, more advantageous over the conventional iodine‐based contrast agents (K‐edge 33 Kev) for high voltage imaging applications.…”
Section: Introductionmentioning
confidence: 99%